Analisis Perwatakan Tokoh dan Konflik Internal Tokoh dalam Novel Me and My Broken Heart Karya Wulanfadi - Senjaya, Yuni; Shomary, Sudirman (UIR Press, 2024)
Not only that, the creation of literary works also leads to high thoughts that are not only formed from mere daydreams. Based on this fact, the author conducted a research with the title